Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems 2018
DOI: 10.1145/3173574.3173677
|View full text |Cite
|
Sign up to set email alerts
|

Explanations as Mechanisms for Supporting Algorithmic Transparency

Abstract: Transparency can empower users to make informed choices about how they use an algorithmic decision-making system and judge its potential consequences. However, transparency is often conceptualized by the outcomes it is intended to bring about, not the specifics of mechanisms to achieve those outcomes. We conducted an online experiment focusing on how different ways of explaining Facebook's News Feed algorithm might affect participants' beliefs and judgments about the News Feed. We found that all explanations c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
185
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(214 citation statements)
references
References 45 publications
5
185
0
1
Order By: Relevance
“…Indeed, some users are not aware of algorithmic ranking on platforms (Eslami et al, 2015;Rader et al, 2018) and, thus, do not even know the game exists, let alone how to play it. This suggests that the game reinforces offline hierarchies of social privilege with 'winners' being those with greater access to social, cultural, political, and economic resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some users are not aware of algorithmic ranking on platforms (Eslami et al, 2015;Rader et al, 2018) and, thus, do not even know the game exists, let alone how to play it. This suggests that the game reinforces offline hierarchies of social privilege with 'winners' being those with greater access to social, cultural, political, and economic resources.…”
Section: Discussionmentioning
confidence: 99%
“…Like other platform owners, Instagram shares few details about the platform's algorithmic architecture or how it works. In general, algorithms function behind the scenes with many users unaware of their presence (Eslami et al, 2015;Rader et al, 2018). Even so, algorithms play an important role in structuring our online experiences (Beer, 2009;Bucher, 2012;Cheney-Lippold, 2011;Gillespie, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has found that explanations often led to more awareness of algorithmic decisions and helped users determine whether a system was biased. It also changed their behaviors toward the system and increased their confidence [16,68]. The possibility of an appeal process for algorithmic systems has received less attention in the literature but would be a rich area for future work.…”
Section: Algorithmic Wishesmentioning
confidence: 99%
“…Transparency is the ability to interpret the information extraction process in order to verify which aspects of the data determine its results. In this context, transparency metrics can use the notions of (i) data provenance [19,18], by measuring the amount of meta-data describing where the original data come from; (ii) explanation [15], by describing how a result has been obtained. Diversity is the degree to which different kinds of objects are represented in a dataset.…”
Section: The Ethics Clustermentioning
confidence: 99%